(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2008)
In this article, the author looks at the changing nature of academic work by analysing a survey of Malaysian faculty in public universities. The Changing Academic Professions project is a first attempt to delineate the opinions and backgrounds of the Malaysian professoriate. The study is part of a larger cross-national project that involves 22 nations. The article first provides literature pertaining to academic work, and then discusses the methodology for the study. The author outlines five topics yielded from the data: (1) faculty mobility, (2) faculty satisfaction, (3) teaching satisfaction, (4) faculty power, and (5) academic freedom. The article then explores the methodological problems of the data and considers how these problems might be overcome in order to provide robust information about the changing professoriate in Malaysia.